(3GdhVY GdbGfhfi dQFjS GdOhdI aj GdbGfhf GdOhdj GdYGe (B/ s - (3eMeO YHOGdeWdH GdNTfs; (3CMeO CHh GdhaG (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2004)
(3JHOC GdQSGdI HHGH JegjOj Yf eONd Edi GdhVY GdbGfhfj dQFjS GdOhdI aj GdbGfhf GdOhdj, Ke GdHGH GdGChd Yf eUGOQ GdhVY GdbGfhfj dQFjS GdOhdI aj GdbGfhf GdOhdj, Ke jCJj GdHGH GdKGfj djJfGhd GNJUGUGJ QFjS GdOhdI aj GdbGfhf GdOhdj, hGdHGH GdKGdK GdPj jJfGhd GeJjGRGJ hMUGfGJ QFjS GdOhdI aj GdbGfhf GdOhdj(B.s
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B2004. s
(3HHdjhLQGajG(B: (3UaMGJ (B385-409.s
Keywords: (3QFjS GdOhdI aj GdbGfhf GdOhdjs; (3GdfXGe GdQFGSjs; (3GdfXGe GdHQdeGfjs; (3GdCfXeI GdedcjIs; (3GdQFGSI GdaQOjIs; (3GdYQa GdOhdjs; (3GdeYGgOGJ GdOhdjIs; (3GNJUGUGJ QFjS GdOhdIs; (3QFjS GdOhdI aj GdbGfhf GdOhdjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- 2004